The Effects of Corporate Social Responsibility on Firm Performance: The Moderating Roles of Firm Innovation Among Manufacturing Companies Listed on the Indonesia Stock Exchange - Adri Putra Nugraha; Astuti, Vina Sri; Fathanudin, Muhammad (Fakultas Ekonomi Universitas Kadiri, 2025)
This study aims to examine the effect of Corporate Social Responsibility (CSR) on firm performance with innovation as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange for the period 2016–2021. CSR is measured based on disclosure according to the Global Reporting Initiative (GRI) standards, while firm performance is assessed through Return on Assets (ROA). Firm innovation is measured using the ratio between R&D expenditure and total sales. The multiple regression analysis method is used to test three hypotheses. The results show that CSR has no significant effect on firm performance, but innovation has a positive and significant impact. When moderated by innovation, CSR positively affects firm performance, indicating that innovation strengthens the effectiveness of CSR. The control variable firm age is not significant, while size and firm growth positively influence firm performance. This study provides important insights into the relationship between CSR, innovation, and firm performance in the Indonesian manufacturing sector, as well as implications for executives, policymakers, and researchers in maximizing firm performance through the integration of CSR and innovation in developing countries